Institutional violence and quality of service in obstetrics are associated with postpartum depression - Souza, Karina Junqueira de; Rattner, Daphne; Gubert, Muriel Bauermann (Revista de Saúde Pública, 2017)
OBJECTIVE To investigate the association between institutional violence in obstetrics and postpartum depression (PP depression) and the potential effect of race, age, and educational level in this outcome. METHODS This is a cross-sectional study about the health care conditions for the maternal and child population of the Federal District, Brazil, carried out in 2011. The study has used a probabilistic sample of 432 women, whose children were aged up to three months, stratified by clusters. Indicators of institutional violence and demographic characteristics have been used in a logistic regression model to estimate the probability of occurrence of postpartum depression. RESULTS The model has identified a high prevalence of postpartum depression, being it higher among non-white women and adolescent females, besides having a strong positive association between the several indicators of obstetric violence and postpartum depression. Positive interactions on a multiplicative scale have also been observed between: violence by negligence by health care professionals and race and age; physical violence from health care professionals and age; and, verbal violence from health care professionals and race. CONCLUSIONS The indicators adopted to reflect institutional violence in obstetric care are positively associated with postpartum depression, which calls for a reflection on the need to make the health care protocols adequate to the precepts of the Brazilian humanization of childbirth care policies and changes in the obstetric care model.